2012
DOI: 10.1063/1.3686432
|View full text |Cite
|
Sign up to set email alerts
|

Rate and temperature effects on the flow stress and tensile strength of metals

Abstract: Some new and obtained earlier experimental data on the elastic precursor decay and rise times of plastic shock waves in several metals and alloys at normal and elevated temperatures are discussed. The time range available for measurements has been expanded to picoseconds that allows approaching ultimate shear and tensile strengths and observations of general trends. Results of measurements have been transformed into dependences of plastic strain rate on the shear stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…These precipitates act to pin dislocations. Similar comparisons in behaviour have also been seen when comparing relatively pure forms of aluminium to that of alloys where the alloys such as precipitation hardened AA 6061-T6 show little-to-no precursor decay [43,44], whereas relatively pure forms of aluminium show moderate decay [44,45]. Further, Winey et al [46] showed that thin (less than 600 μm) 1050 Al samples exhibited attenuation of the elastic precursor, whereas the AA 6061-T6 targets did not.…”
Section: (A) Shock Response Of Magnesiumsupporting
confidence: 56%
“…These precipitates act to pin dislocations. Similar comparisons in behaviour have also been seen when comparing relatively pure forms of aluminium to that of alloys where the alloys such as precipitation hardened AA 6061-T6 show little-to-no precursor decay [43,44], whereas relatively pure forms of aluminium show moderate decay [44,45]. Further, Winey et al [46] showed that thin (less than 600 μm) 1050 Al samples exhibited attenuation of the elastic precursor, whereas the AA 6061-T6 targets did not.…”
Section: (A) Shock Response Of Magnesiumsupporting
confidence: 56%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In this regard, shock-wave studies of the dynamic yielding and fracture of single crystals occupy a special place, since they allow the separation of contributions of different mechanisms of nucleation and the growth of plastic deformation and fracture and such experiments are useful for verifying molecular dynamic simulations. During recent decades, shock-wave studies of the dynamic yielding and fracture of metal single crystals have been performed on face-centered cubic (fcc) metals; such as copper [13][14][15][16] and aluminum, [17][18][19][20] body-centered cubic (bcc) metals, such as molybdenum; 21 and hexagonal close-packed (hcp) metals, such as beryllium 22 and zinc.…”
mentioning
confidence: 99%
“…According to papers written by G.I. Kanel' with coworkers [6,[19][20][21] the value of HEL varies. For example, the value depends on the time (and vice versa) during which the uniaxial load σ xx is maintained in elastic solid.…”
Section: Nd International Symposium On Shock Waves (Issw32)mentioning
confidence: 99%